MENGUKUR KEPUASAN PELAYANAN PUBLIK INSTITUSI PEMERINTAH: STUDI KASUS PADA BUMN PT. JAMSOSTEK (PERSERO) - Abdul Rahman (Jurnal Borneo Administrator, 2009)
Strive to improve and take care of quality of service is not easy work, and surely if party in concerned at that service is plenty of. Program JPK, as one of public service program in health area which is carried out a government, in this case BUMN PT Jamsostek (Persero), embracing pattern three partit entangling tripartite that is Organizer (PT Jamsostek), Provider ( Executor of Health Service) and Consumer (Institution and employees). This Three partit pattern represent the complex model because each part have the separate problem potency. Interaction from all part  has potency to peep out the other problem which in the end can influence quality of service to consumers and its family member.  To measure the service satisfaction which have been given objectively in order to improving and taking care of service quality, this study is done and  its result indicate that most consumers (73,1%) expressing to satisfy to health service  from JPK Program of PT. Jamsostek (persero).  Kata Kunci: Program JPK, Tripartit, Pelayanan, Kepuasan Konsumen